2021
DOI: 10.1186/s41100-021-00323-1
|View full text |Cite
|
Sign up to set email alerts
|

Filter lifetimes of different hemodiafiltration membrane materials in dogs: reevaluation of the optimal anticoagulant dosage

Abstract: Background In continuous renal replacement therapy (CRRT), administration of anticoagulants is necessary for achieving a certain level of filter lifetime. Generally, anticoagulant doses are controlled to keep activated partial thromboplastin time and other indicators within a certain target range, regardless of the membrane materials used for the filter. However, in actual clinical practice, the filter lifetime varies significantly depending on the membrane material used. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although the PMMA hemofilter was reported to adsorb the proinflammatory cytokines well, as described above, coagulation in hemofilters during blood purification due to chemostructural changes in membrane surface was found to be a complication [27]. Therefore, a high dose of the anticoagulant nafamostat mesilate was required [28]. Theoretically, CHF was considered to be effective for adsorbing cytokines [29], and it was reported that the use of CHF was significantly expensive compared with the use of CHD [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the PMMA hemofilter was reported to adsorb the proinflammatory cytokines well, as described above, coagulation in hemofilters during blood purification due to chemostructural changes in membrane surface was found to be a complication [27]. Therefore, a high dose of the anticoagulant nafamostat mesilate was required [28]. Theoretically, CHF was considered to be effective for adsorbing cytokines [29], and it was reported that the use of CHF was significantly expensive compared with the use of CHD [30].…”
Section: Discussionmentioning
confidence: 99%